Massive nutrients offshore transport off the Changjiang Estuary in flooding summer of 2020 - Qianwen Sun; Dewang Li; Bin Wang; Zhongsheng Xu; Yanyi Miao; Hua Lin; Haiyan Jin; Zhibing Jiang; Jiangning Zeng; Feng Zhou; Jianfang Chen (Frontiers in Marine Science, 2023)
Flood events significantly increase water discharges and terrigenous material inputs to coastal waters. Riverine nutrients in the Changjiang Estuary are transported by the dispersion of Changjiang Diluted Water (CDW) plumes and detached low-salinity water patches. However, the effects of flooding on nutrient offshore transports have not been well explored. Here, we present the nutrient conditions in the Changjiang Estuary and adjacent East China Sea in the historical flooding year 2020. Comparisons of nutrient distributions between flooding years, drought year and non-flooding years were also made. Our results showed that nitrate flux from the Changjiang River in August 2020 was 1.5 times that of the multi-year averaged flux in non-flooding years. Enormous riverine nutrient input resulted in much higher nutrient concentrations in the outer estuary than those in non-flooding years. In addition, a detached low-salinity water patch was observed, which made the salinity of the northern estuary even lower than that in the historical flooding year 1998. Surface dissolved inorganic nitrate (DIN) level in the low-salinity water patch was even ~16 times of that at nearby station in the drought year 2006. While phosphate (PO 4 3− ) concentrations were less than 0.1 μmol L −1 east of 123°E, which was probably caused by intensive biological uptake, as indicated by a high Chlorophyll a (Chl a ) concentration (29.08 μg L −1 ). The depleted PO 4 3− and high N/P of the low-salinity water patch suggested PO 4 3− limitation even under flood conditions. A three end-member mixing model was adopted to identify the contributions of the CDW end-member (CDW end-member ) and biological process to nutrient distributions. Our model results showed that the nutrient contribution of the CDW end-member to the estuary (122–124°E, 31–32.5°N) in flooding year 2020 was over double that in drought year 2006. Model-derived biological DIN uptake was as high as 24.65 μmol L −1 at the low-salinity water patch. Accordingly, the estimated net community production was 566–1131 mg C m −2 d −1 within the euphotic zone. The offshore transport of a low-salinity, high-DIN water patch during flooding could probably have a significant influence on biogeochemical cycles in the broad shelf, and even the adjacent Japan Sea.